Modeling of electromagnetic field in the Earth-ionosphere resonator (Transmission Line Method) - KOSTECKÝ, Pavel; ONDRÁŠKOVÁ, Adriena; ROSENBERG, Ladislav; KOHÚT, Igor (Contributions to Geophysics and Geodesy, 2021)
The Schumann resonances – electromagnetic eigenmodes of the resonator bounded by the Earth’s surface and lower ionosphere, permanently excited by the global lightning activity – are now widely monitored experimentally. To relate the obtained data with ionospheric parameters the computer modeling of such a resonator is necessary. The various approaches to this task are surveyed and some new insights are suggested.